Improving the Production System in a Customized Furniture Industry: A Case Study - Silva, Inês; Regattieri, Carlos; Lucas, Rafael [UNESP]; Sebbe, Naiara; Sales-Contini, Rita (Springer Nature, 2025)
Furniture factories face numerous challenges in a rapidly growing market due to rising costs, fluctuating demand and changing consumer preferences, which means they must adapt quickly to new designs and trends. Additionally, the growing environmental concern creates the need for sustainable production methods, while keeping profit margins and high productivity. A study in the furniture industry aimed to optimize production systems, reduce waste, and increase productivity by identifying bottleneck workstations, excessive transportation and long setup times. The layout restructuring and the implementation of Lean tools, such as 5S, visual management methods and SMED methodology (Single Minute Exchange of Dies), led to significant reductions in transportation and lead time. The Action-Research (AR) methodology was also used as a strategy to detect the critical points of the process. The strategic positioning of equipment, workstations and storage locations simplified material flow, resulting in a 31% reduction in transportation times. The conversion of some internal to external activities of preparation tasks allowed for a 29% reduction in setup times for production lines, increasing flexibility and productivity. Overall, this study demonstrated that Lean tools positively impact global efficiency, increasing productivity and sustainability.